Balanced scorecard :prestasi keberkesanan pengurusan dan pemasaran produk kraftangan etnik berawan dan penan di taman negara Mulu - Paul, Ajang. (UNIMAS, 2009)
The purpose of this research is to study the achievement in effectiveness performance of management and marketing in traditional crafts. The units’ analyses are Berawan and Penan ethnic in Mulu National Park. Balanced scorecard model (Kaplan & Norton, 1992) has been apllied in this study to identify the opportunities to develop the management skill in craft industry. The quantitative method was carried out by spreading questionnaire to Berawan and Penan ethnic craft maker has been used in this research. The questionnaire contains 27 items with 5 likert scale answer. Technical method offrequency,crosstabulation, meansand correlation pearsonhas been used to analyses the data. The result on this research and hypothesis testing show that: there are no relationships between four perspectives accepted consumer and financial perspective in balanced scorecard model with performance in management and marketing of Berawan and Penan ethnic craft.